Use Of Life Cycle Assessment Reference Method To Improve Life Span Of Roads In Maseru - Monts’i, Moliehi (Central University of Technology, Free State, 2019)
Poor road infrastructure in Lesotho has led to investigating the failure reasons and solutions to improving the transportation sector using life cycle assessment reference method. Life Cycle Assessment is an evaluation of pavement products from manufacturing to demolition. A critical review of Lesotho laws and policies was done. These laws and policies governing the construction of roads sector were studied to review how the road construction is to be carried out in Lesotho. The expectations from the government concerning the transportation sector were reviewed. There has been a gap in that the government being the main client, as the construction does not fulfill the long term needs of communities. The literature reviews, questionnaires, interviews, observations and case studies were carried out to develop a framework to eliminate the early failure of roads. It concentrated mainly on the environmental impacts on the pavement product. For both economic prosperity and personal mobility, roads are a basic need in infrastructure systems. Life Cycle Assessment is being integrated daily in different disciplines to achieve sustainable practices that include the road construction sector. It studies the environmental impacts and helps predict future circumstances. This study elaborates on ways to improve current situations to meet future economic needs. This study quantifies the environmental impacts of a product, in this case, road construction. It is used to assess the environmental issues to enhance prolonged pavement life in the Lesotho roads.
Dissertation